Evaluation of some biomechanical indicators of the spiking skill performance of local players and professional volleyball players in the Premier League - Abdullah Hnaihen, Hassan; Abdel Rahman, IYad (University of Thi-Qar Journal, 2024)
The purpose of this paper is to identifying the differences between the values of some biomechanical indicators of the skill of spiking in volleyball between local players and professional players in Premier League clubs , and identifying the relationship between some biomechanical indicators and the performance accuracy of some offensive skills in volleyball among local and professional players in the Iraqi Premier League clubs. The researchers used the descriptive method in the survey method, the comparative method, and the correlations, which is consistent with the nature of the research problem. research community represented by the players of the Iraqi Premier League clubs in volleyball who qualified for the Golden Square, which numbered (56) players for the sports season (2022/2023), was identified. As for the research sample, it was chosen by the intentional method as well, and they are the players of the clubs (Erbil, South Gas, Peshmerga, Al-Shorta), and their number is (12) players (6) professional players (6) local players, and they represent (21.42%) of the community. the origin. One of the most important results reached by the researcher is that: The values of the momentum index and kinetic energy achieved by the professional players are due to the mass and velocity index, as the mass and velocity values of the professional players were higher than the local players in the spiking skill. One of the most important recommendations recommended by the researchers is that: Necessity of emphasizing by the coaches on developing the values of the biomechanical indicators of the skill of spiking for the local players. Which showed a clear decrease in all biomechanical indicators compared to professional players.